Alkylethoxyglucoside-enhanced volatile fatty acids production from waste activated sludge: performance and mechanisms - Wu, Qinglian (2022)
The green and low-cost surfactant Alkylethoxyglucoside (AEG) was used to enhance VFAs production from waste activated sludge (WAS). VFAs production (436.27 ± 14.88 mg COD/g VSS) was improved by ∼6.15 times than the blank under the optimal dosage 0.4 g/g TSS, exceeding most of current enhancement strategies. Thereinto, AEG degradation contributed to ∼15% of total VFAs production, and its primary degradation rate approached 100% on the eighth day. Mechanism investigation revealed that AEG promoted the WAS disintegration and enzyme-substrate interaction by reducing the surface charge to weaken the repulsive force, so that hydrolysis and acidification extents were improved by 35% and 18%, respectively. However, methanation was suppressed by AEG itself and the reduced pH. Additionally, the functional microorganisms responsible for substrates hydrolysis and VFAs generation were much more enriched after adding AEG. From a performance, economic and environmental perspective, AEG has a great application potential on enhancing VFAs production.